2017
DOI: 10.1038/ijos.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

An early report: a modified porphyrin-linked metronidazole targeting intracellular Porphyromonas gingivalis in cultured oral epithelial cells

Abstract: Porphyromonas gingivalis (P. gingivalis) has a strong association with the pathogenesis of periodontal disease. Recurrence of periodontal disease following therapy is attributed to numerous factors, and of growing interest is the potential problem of intracellular bacteria that are able to persist and multiply within the host cell, thereby facilitating relapse of infection. The effect of antibiotic therapy in controlling P. gingivalis is questionable. Accordingly, while metronidazole is very effective against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Although CLM has not been widely used in periodontal therapy, it was shown to be effective against “Aa” and several other periodontal pathogens, as it can reach bacteria that have invaded oral epithelium. [31] In combination with results from previous studies,[323334] the current findings suggest that CLM could be useful for treating periodontitis. However, an affirmative effect of CLM is very narrow.…”
Section: Discussionsupporting
confidence: 79%
“…Although CLM has not been widely used in periodontal therapy, it was shown to be effective against “Aa” and several other periodontal pathogens, as it can reach bacteria that have invaded oral epithelium. [31] In combination with results from previous studies,[323334] the current findings suggest that CLM could be useful for treating periodontitis. However, an affirmative effect of CLM is very narrow.…”
Section: Discussionsupporting
confidence: 79%
“…MET promotes free-radical formation that interacts with bacteria DNA, resulting in loss of the helical DNA structure and strand breakage. 55 On the other hand, tetracycline, a broad-spectrum antimicrobial, inhibits bacterial protein synthesis. As an additional advantage, tetracyclines can inhibit collagenase, 56 contributing to minimizing tissue breakdown.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Metronidazole (MET), as an antibiotic, can cause strand damage to the bacterial DNA through the reduction of its nitro-group by an electron transport protein. 299 Madadi et al reported that conjugated cCQD-MET could rapidly internalize into H413 cells and exhibit enhanced antimicrobial activity. 300 In a different study, the CDs@PtPor composite demonstrated strong photocytotoxicity under light irradiation and therapeutic efficacy as well as low side effects in vitro , which was developed as a drug nanocarrier in cancer therapy.…”
Section: Composites For Biomedical Applicationsmentioning
confidence: 99%
“…For instance, in Yan and co-workers’ study, glyoxylic acid-modified CDs (GA-CDs) were used as a FRET ratiometric fluorescent probe for the detection of Cu 2+ in aqueous solution. 388 Similarly, Chen et al also applied cyclam-functionalized CDs as a FRET nanoprobe for the detection of Cu 2+ and S. 2–389 In addition to the above examples, the detection of other important metal ions such as Ag + , Cu 2+ , Cr 6+ , and Pb 2+ has also been successfully realized with CD composite-based sensing platforms. 390–401…”
Section: Composites For Biomedical Applicationsmentioning
confidence: 99%